Neuromechanical Differences Between Successful and Failed Sit-to-Stand Movements and Response to Rehabilitation Early After Stroke. (May 2019) - Kerr, Andy; Clark, Allan; Pomeroy, Valerie M.
Background . Recovery of the sit-to-stand (StS) movement early after stroke could be improved by targeting physical therapy at the underlying movement deficits in those people likely to respond. Aim . To compare the movement characteristics of successful and failed StS movements in people early after stroke and identify which characteristics change in people recovering their ability to perform this movement independently following rehabilitation. Methods . Muscle activity and kinematic (including center of mass, CoM) data were recorded from 91 participants (mean 35 days after stroke) performing the StS movement before (baseline), immediately after (outcome), and 3 months after (follow-up) rehabilitation. Three subgroups (never-able [n = 19], always-able [n = 51], and able-after-baseline [n = 21]) were compared at baseline with the able-after-baseline subgroup compared before and after rehabilitation. Results . The subgroups differed at baseline for quadriceps onset time ( P = .009) and forward body position when quadriceps peaked ( P = .038). Following rehabilitation, the able-after-baseline subgroup increased their forward position ( P < .001), decreased the time difference between bilateral quadriceps peaks ( P < .001) and between quadriceps and hamstrings peaks on the nonhemiplegic side ( P = .007). An improved performance in the always-able subgroup was associated with a number of baseline factors, including forward positioning ( P = .002) and time difference between peak activity of bilateral quadriceps ( P = .001). Conclusions . This neuromechanical study of StS before and after rehabilitation in a sample of people early after stroke identified the importance of temporal coupling between forward trunk movement and quadriceps and hamstrings' activity. These findings advance the science of stroke rehabilitation by providing evidence-based therapy targets to promote recovery of the StS movement.